Extended Family Health Center from the perspective of Community Health Agents - Miranda, Bárbara Aline de Bezerra; Pegoraro, Renata Fabiana (Interação em Psicologia, 2021)
The complexity of primary health care provided in the context of family health units led to the implementation of Núcleos Ampliados de Saúde da Família [Extended Family Health Centers], composed of medical specialists, responsible for providing clinical, sanitary and teaching support to the reference team. This paper presents the perceptions of community health agents regarding the Extended Family Health Center (NASF-AB). Thirteen female agents working in two family health teams in the state of Minas Gerais, Brazil responded to a sociodemographic questionnaire and a semi-structured interview addressing their experience and relationship with the NASF-AB. The following thematic axes emerged: (1) Report and refer cases to one or more NASF professional; (2) Community health agents discuss cases with the NASF-AB staff and receive guidance; (3) Joint home visits; (4) the role of the NASF-PHC. The participants perceive the NASF-PHC as a team of specialists who receive referrals and provide group care. Matrix support is under development and not all professionals are recognized as being members of NASF-AB staff. We conclude that there is a need to value the work of community health agents and implement permanent education actions.